Comparative Examination of Challenges and Development in Anti-Corruption Measures in Public Procurements of Nigeria, China and Brazil - Nnawulezi, Uche; Kabano, Jacques (Journal of Law and Corruption Review, 2025)
Purpose: This study provides a comparative analysis of the challenges and developments of anti-corruption measures in public procurement processes in Nigeria, China, and Brazil, focusing on regulatory frameworks, institutional mechanisms, and practices aimed at enhancing transparency, integrity, and accountability. Method: The research adopts a qualitative doctrinal approach, based on the analysis of national legislation, international treaties, reports from multilateral organizations, and specialized academic literature. A comparative method is employed to identify similarities, differences, and limitations of anti-corruption regimes in public procurement across the three countries. Findings: The findings reveal that despite relevant normative advances, significant weaknesses persist in the implementation and enforcement of anti-corruption measures. Nigeria faces institutional capacity constraints and limited adoption of e-procurement systems. China exhibits a centralized and punitive approach, with notable progress in digital tools, but ongoing transparency challenges. Brazil presents a relatively robust legal framework and advanced electronic procurement systems, although enforcement gaps and coordination issues remain. Originality/Value: The study advances the literature by demonstrating that effective anti-corruption strategies in public procurement require not only legal reforms, but also institutional strengthening, international cooperation, and the strategic use of digital technologies.